Surgical management of breast cancer in China: the Fudan University Shanghai Cancer Center experience - Liu, Xi-Yu; Gou, Zong-Chao; Cao, Zhi-Gang; Jiang, Yi-Zhou; Shao, Zhi-Ming (Translational Cancer Research; Vol 6, No 3 (June 30, 2017): Translational Cancer Research, 2017)
Breast cancer is the most frequently diagnosed cancer in Chinese women, and early-stage patients are significantly increasing. Surgery is the main treatment for early-stage breast cancer with the “minimally invasive procedures” concept. The modality of breast cancer surgery has changed greatly in recent years in China, especially in our cancer center, Fudan University Shanghai Cancer Center (FUSCC). Firstly, pre-surgery biopsy is a routine procedure, which is mainly assisted by imaging instruments. Secondly, the number of breast-conserving surgery (BCS) and simple mastectomy procedures with or without sentinel lymph node biopsy (SM ± SLNB) is increasing gradually; radical mastectomy (RM) and modified radical mastectomy (MRM) are decreasing annually. Thirdly, SLNB has become a routine procedure in our center; it is safe and effective for replacing axillary lymph node dissection (ALND). Finally, reconstruction surgery has progressively advanced, although the operation cases are limited. This review article looks back at the development of breast cancer surgery, highlights the hallmarks of surgical management in our center as well as in China and discusses the future necessary efforts to improve the outcome and life quality for Chinese patients.